2014
DOI: 10.1002/hc.21250
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study on the Stability and Aromaticity of Heterobenzenes Containing Group 15 Elements

Abstract: The stability and aromaticity of 36 heterobenzenes containing group 15 elements were evaluated at the B3LYP/6‐311+G(d,p) level of theory. Stability evaluation was performed based on the enthalpies of formation calculated from imaginary reactions and on the absolute hardness reactivity descriptor. The aromaticity was investigated by means of geometric (Bird, Harmonic Oscillator Model of Aromaticity (HOMA) indices), energetic (aromatic stabilization energy), and magnetic criteria (nucleus‐independent chemical sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…Among other criteria, it is known that nucleus-independent chemical shift values calculated 1 Å above the corresponding RCPs (NICS(1)), black dots in Figure , provide a good measure of the aromaticity/π electron delocalization along a ring. , Typical NICS(1) values, in parts per million, are ca. −10.2 for benzene, the paradigm of an aromatic ring, , −10.1 for pyridine, , and −10.8 (rings 1 and 2) and −8.4 (ring 4) for isolated phen . In this work, NICS(1) values for phen at [Re­(PPh 2 ) (CO) 3 (phen)] (−10.1, −10.3, and −8.7 ppm for rings 1, 2, and 4 in Table S10, respectively) are similar to those mentioned above for the isolated ligand.…”
Section: Resultssupporting
confidence: 81%
“…Among other criteria, it is known that nucleus-independent chemical shift values calculated 1 Å above the corresponding RCPs (NICS(1)), black dots in Figure , provide a good measure of the aromaticity/π electron delocalization along a ring. , Typical NICS(1) values, in parts per million, are ca. −10.2 for benzene, the paradigm of an aromatic ring, , −10.1 for pyridine, , and −10.8 (rings 1 and 2) and −8.4 (ring 4) for isolated phen . In this work, NICS(1) values for phen at [Re­(PPh 2 ) (CO) 3 (phen)] (−10.1, −10.3, and −8.7 ppm for rings 1, 2, and 4 in Table S10, respectively) are similar to those mentioned above for the isolated ligand.…”
Section: Resultssupporting
confidence: 81%
“…The stability and aromaticity are related concepts, and thus, some of the DFT descriptors can be discussed to analyze aromaticity. Table lists the energies of the HOMO, the LUMO, energy gap ( E g ), vertical IP, and EA as well as η, S , χ, μ, and ω. From Table , it has been found that the keto form has the lowest HOMO–LUMO gap (2.30 eV) followed by enol forms (3.08 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Analogues of benzene where one CH group is formally replaced by a main group element are well known and in many cases have been shown to retain a significant degree of aromatic character . Some notable examples from recent years include bisma‐, alumina‐, sila‐, germa‐ and stannabenzenes …”
Section: Metallabenzenesmentioning
confidence: 99%